The Effect of Stroke Up and Bore Up on The Performance of Honda Verza Motorcycle - damayanti, lydia; Septiyanto, Angga (Jurnal Inovasi Mesin, 2024)
Many young people make bore up and stroke up modifications to improve the performance of their motorbike engines. which is used for daily activities and racing contests. Apart from that, this modification is necessary for some people, especially men, because most of the people in Juwana work as farmers in fish ponds. Apart from that, the condition of the roads in the pond is still dirt, which makes the roads muddy when it rains. Because motorbikes are used to transport fish harvests and as transportation, their motorbikes also require more power. This research uses an experimental research design by changing the stroke length and piston diameter on a Honda Verza motorbike with variations of Stroke Up, Bore Up and Stroke Up Bore Up. With testing steps using a dynotest 3 times on each motorbike variation to determine the performance of the Honda Verza motorbike. The results of this research show an increase in torque and power produced after modifying the stroke up and bore up. The resulting modification of increasing the piston diameter (bore up) affects the torque and power values produced by the Honda Verza motorbike. The torque value increased by 1.34% at 10,000 rpm and the power value increased by 1.39% at 13,000 rpm. Meanwhile, the stroke up variation affected the power and torque produced by the Honda Verza motorbike. The results obtained from testing the stroke up engine experienced an increase in torque value of 1.36% at 11000 rpm and the power produced increased by 3.16% at 13000 rpm